2012
DOI: 10.1158/1078-0432.ccr-12-0736
|View full text |Cite
|
Sign up to set email alerts
|

Anti-DLL4 Has Broad Spectrum Activity in Pancreatic Cancer Dependent on Targeting DLL4-Notch Signaling in Both Tumor and Vasculature Cells

Abstract: Purpose: We previously showed that targeting Delta-like ligand 4 (DLL4) in colon and breast tumors inhibited tumor growth and reduced tumor initiating cell frequency. In this report, we have extended these studies to pancreatic cancer and probed the mechanism of action in tumor and stromal cells involved in antitumor efficacy.Experimental Design: Patient-derived pancreatic xenograft tumor models were used to evaluate the antitumor effect of anti-DLL4. To investigate the mechanism of action, we compared the act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 53 publications
1
50
0
1
Order By: Relevance
“…3C). Moreover, hepatoma cells expressing cyclin G1 exhibit enhanced tumor initiating capacity (27) in NOD-SCID mice compared with the control cells (Table 1 and Fig. 3D).…”
Section: Cyclin G1 Promotes the Expansion Of Liver T-ics In Hepatoma mentioning
confidence: 90%
“…3C). Moreover, hepatoma cells expressing cyclin G1 exhibit enhanced tumor initiating capacity (27) in NOD-SCID mice compared with the control cells (Table 1 and Fig. 3D).…”
Section: Cyclin G1 Promotes the Expansion Of Liver T-ics In Hepatoma mentioning
confidence: 90%
“…Our findings are consistent with the previous observations that inhibition of Dll4 increased TAEC number, which results in excessive angiogenic sprouting and branching with disordered tumor vascular geometry. [13][14][15][16][17] There is growing interest in combining antiangiogenic agents in an effort to enhance tumor cell starvation and to overcome issues of resistance. 36 One intriguing approach would be to simultaneously suppress both angiopoietin-Tie2 and Dll4-Notch signaling pathways; this may enhance the suppression of functional angiogenesis within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] In contrast, several studies have shown that administration of an anti-Dll4-specific antibody stimulates the proliferation of endothelial tip cells and increases vascular density in human tumor xenografts. [13][14][15][16][17] However, this is believed to contribute to tumor starvation and suppression of tumor growth as inhibition of Dll4-Notch signaling results in the formation of nonfunctional immature vessels leading to poor tumor perfusion.…”
mentioning
confidence: 99%
“…Specifically, inhibition of DLL4 signaling during angiogenesis disrupts the dynamic balance between tip and stalk cells (10), resulting in a chaotic vascular network characterized by excessive sprouting and branching, dramatically reduced vessel lumen size, and increased vascular density (11)(12)(13). DLL4 neutralizing (anti-DLL4) antibodies have been associated with robust antitumor activity in a wide range of preclinical efficacy models (14)(15)(16)(17)(18), likely by promoting nonproductive angiogenesis that impairs tumor microcirculation and induces hypoxia (19,20). In addition to the potent antitumor activity observed following anti-DLL4 treatment, additive antitumor activity has also been observed in combination with anti-VEGF therapy and/or chemotherapy (14,(16)(17)(18)21).…”
Section: Introductionmentioning
confidence: 99%
“…DLL4 neutralizing (anti-DLL4) antibodies have been associated with robust antitumor activity in a wide range of preclinical efficacy models (14)(15)(16)(17)(18), likely by promoting nonproductive angiogenesis that impairs tumor microcirculation and induces hypoxia (19,20). In addition to the potent antitumor activity observed following anti-DLL4 treatment, additive antitumor activity has also been observed in combination with anti-VEGF therapy and/or chemotherapy (14,(16)(17)(18)21). Based on the important role of DLL4 in vascular biology as well as the broad preclinical antitumor activity of anti-DLL4 monoclonal antibodies, several anti-DLL4 molecules are currently being investigated in clinical trials as potential cancer therapeutics (22).…”
Section: Introductionmentioning
confidence: 99%